Identidades narrativas y organizaciones juveniles en sectores populares de Cali (2023)
This study falls within social constructionism from a narrative perspective. Its overall objective is to identify some elements of narrative identities associated with participation in youth organizations. It is a narrative design, purposive sampling, exploratory qualitative research. Eleven young people between 20 and 26 years old living in Cali, Colombia participate in the study. To collect data, semi-structured interviews and discussion groups are used. Textual and categorical analyses are performed by ATLAS.ti 7.0 software. The results of the Self- Conception category shows the continuous negotiation of self-image and the creation of a place of recognition in the sociocultural context. The Life Project category suggests street and music as semiotic spaces where life goals are created in the context of everyday relationships. In conclusion, it can be said that stories are contextualized but reflect how young people re-create and subvert their sociopolitical realities.